Women’s experiences of low back pain during pregnancy - Mota, Maria João (2016)
OBJECTIVES: This study investigated the self-reported prevalence and impact of low back pain (LBP) during pregnancy in primiparous and multiparous women, and their treatment-seeking rationales and experiences, including their use of physiotherapy. METHODS: A sample of 105 post-partum women was recruited. All participants answered a questionnaire; women who experienced LBP during pregnancy (n=71) continue in the study and later they were also interviewed. Content analysis, descriptive and inferential statistics were used to analyse the data. RESULTS: Reports of LBP were common (n=71; 67.6%) and slightly more frequent in primiparous (n=40; 56.3%) than multiparous (n=31; 43.7%) women. Multiparous women with LBP were significantly older (p< 0.001) and reported more sleep disturbances (p=0.026) than primiparous women with LBP. LBP prevented women performing their daily activities (n=41; 57.7%) and worsened with the advance of pregnancy (n=55; 77.5%), yet 93.0% (n=66) of these women received no treatment. CONCLUSION: LBP is a prevalent and important clinical condition affecting the daily life of many pregnant women. Nevertheless, few women seek any treatment and physiotherapy is rarely considered. Given the significant impact on quality of life, health professionals need to be proactive in asking women about LBP.